CRITICAL INFRASTRUCTURE (CI) PROTECTION FOR FLOOD RISK ASSESSMENT AND FLOOD VULNERABILITY INDEX IN SUNGAI PINANG, PULAU PINANG (Malaysian Journal of Civil Engineering, 2023)
Infrastructure that is rated "critical" has a significant long-term impact on a large number of people when it fails.  This study's objective is to rank Sungai Pinang's Critical Infrastructure (CI) for flood risk assessment and vulnerability index. According to the literature research, there are seven (7) indicators that are linked to CI, including industrial areas, infrastructure and utilities, institutions and public facilities, commercial areas, transportation, residential areas, and open space and recreational areas. Experts from local governments and technical agencies in the state of Pulau Pinang that are concerned with and related to CI ranked the indicators during the focus group discussion. The most significant degree of CI was used to order these indicators. According to the results, residential areas received the maximum score of 165 points. With a total score of 160, institutions and public buildings are the second-ranked indicator. Infrastructure and utilities, which are ranked third, received 102 points, while transportation, which is ranked fourth, received 100 points. The fifth-ranked indication is commercial areas (65 marks). Open space and recreational areas are the indicator that came in sixth (64 marks). Industrial area ranks last among the indicators (58 marks).